Pengaruh Konflik Keagenan Mengenai Kebijakan Dividen terhadap Konservatisma Akuntansi - A. A. G. P. Widanaputra (Jurnal Aplikasi Manajemen, 2012)
This research tests the impact of the conflict between shareholder and management regarding dividend policy on accounting conservatism. This conflict is predicted under agency problem on the agency theory that shows conflicts of interest between management (agent) and shareholders (principal). This research also test the difference in accounting conservatism between companies that are managed by owner-manager.This research use regression analysis to test the impact of conflict between shareholder and management regarding dividend policy on accounting conservatism, and using leverage, operating uncertainty, investment opportunity set, and size as control variables. This research used t-test to investigate the difference between companies with owner-manager and non owner-manager.The result of the analysis indicates that the conflict between shareholder and management regarding dividend policy has a positive and statistically significant on accounting conservatism. The result also indicates that non ownermanager companies are more conservative than owner-manager companies.Keywords: dividend policy, conservative, agency problem, and conflicts of interest.